Hypothalamic–pituitary–adrenal (HPA) axis function in 3-month old infants with prenatal selective serotonin reuptake inhibitor (SSRI) antidepressant exposure - Oberlander, Tim F. (Early Hum Dev, 2008)
BACKGROUND: Prenatal exposure to stress and selective serotonin reuptake inhibitors (SSRIs) alter hypothalamic–pituitary–adrenal (HPA) stress reactivity in offspring, however, the effects of combined exposure to HPA activity in human infants is unknown. OBJECTIVE: To examine HPA basal levels and stress responsiveness in 3-month olds with prenatal exposure to SSRIs. METHODS: Salivary cortisol levels in infants of SSRI treated mothers (n=31, mean exposure 230.2± 72.2 days) were compared with non-SSRI exposed (n=45) infants in response to a challenge (infant-controlled habituation task) and under basal conditions in the late afternoon/early evening. Mode of feeding, to account for possible postnatal drug exposure via breast milk, as well as measures of pre and postnatal maternal mood, were included as covariates. RESULTS: Lower post-stress cortisol levels were observed in non-SSRI exposed/non-breastfed infants compared with non-SSRI exposed infants who were breastfed at 3 months of age. Stress reactivity patterns among SSRI exposed infants did not differ with mode of feeding. The cortisol reactivity slope (CRS) was significantly lower among non-SSRI exposed non-breastfed infants compared with non-SSRI exposed breastfed infants. Early evening basal cortisol levels were lower in SSRI exposed infants than in non-SSRI exposed infants, controlling for maternal mood and mode of feeding. Postnatal SSRI exposure (infant SSRI drug levels) via breast milk was not associated with stress or basal cortisol levels. Total cortisol, reflected by the AUC measure, did not differ significantly between exposure groups. CONCLUSIONS: Prenatal SSRI exposure altered HPA stress response patterns and reduced early evening basal cortisol levels. Stress challenge HPA response differences only became apparent when the moderating effect of method of feeding was accounted for. These findings suggest an early “programming” effect of antenatal maternal mood, prenatal SSRI exposure and postnatal maternal care giving on the HPA system.